Changes in waist circumference and the prevalence of abdominal obesity during 1994-2008 - cross-sectional and longitudinal results from two surveys: the Tromsø Study - Jacobsen, Bjarne K.; Aars, Nils Abel (BMC Obesity, 2016)
Background: Abdominal obesity increases all-cause mortality and is a risk factor for a number of diseases. There are few population-based studies of the longitudinal changes of abdominal obesity. Methods: Based on data from the Tromsø Study, we studied gender- and age-specific mean waist circumference and prevalence of abdominal overweight and abdominal obesity in two surveys in 1994–1995 (Tromsø 4, 6812 men and women aged 25 to 84) and 2007–2008 (Tromsø 6, 12,493 men and women aged 30 to 87). Furthermore, we describe the longitudinal changes of waist circumference and abdominal obesity during 13 years in 3144 subjects (aged 25–69 in 1994) who attended both surveys. Results: Cross-sectional analyses found a higher mean waist circumference in men than women and a direct relationship with age in both men and women in both Tromsø 4 and in Tromsø 6. As the WHO cut-off points for abdominal obesity are gender-specific, however, the prevalence of abdominal obesity was lower in men than in women. In 2007–2008, approximately 37 and 55 % of men and women, respectively, were classified as abdominally obese. Thirteen years before, in 1994–1995, the corresponding figures were 20 and 35 %. Longitudinal analyses of changes during the 13-year period clearly demonstrated that mean waist circumference increased in all examined birth cohorts in both men (mean change 6.1 cm) and women (mean change 8.4 cm), but increased more markedly the younger the subjects were. The prevalence of abdominal obesity in men aged 25–34 increased from 5 % in 1994 to 31 % 13 years later. The prevalence of abdominal obesity more than doubled among both men and women. Conclusions: The increasing mean waist circumference is of concern. There is a need for further longitudinal studies of the changes in waist circumference